Ensure sustainable consumption and production patterns - Arab Hoballah; Sandra Averous (UN Chronicle, 2015)
Goal 12 of the sustainable development goals (SDGs) proposed by the Open Working Group (OWG) of the General Assembly of the United Nations is aiming at ensuring sustainable consumption and production (SCP) patterns. Why is this an imperative for sustainable development?